Orginal paperThe effect of cross-linking base on the properties of hydrogels with Carbopol and on pharmaceutical availability of morphine sulphate - Samczewska, Grażyna; Kołodziejska, Justyna; Ciałkowska-Rysz, Aleksandra; Piechota-Urbańska, Magdalena (Archives of Medical Science, 2007)
Introduction: The presence of opioid receptors in pathologically changed skin justifies undertaking trials of pain treatment with morphine preparations designed for topical application. The aim of the study was to investigate the effect of selected substances neutralizing carboxyl groups of polyacrylic acid (sodium and potassium hydroxide, trietanoloamine, borax) on physicochemical parameters of the produced hydrogels with Carbopol 980 and Carbopol Ultrez 10 and on pharmaceutical availability of morphine sulphate. Material and methods: There were prepared variant hydrogels with morphine sulphate on the base of Carbopol 980 and Carbopol Ultrez 10. Extensometric method was used to test spreadability of the preparations, gravimetric method to determine the rate of volatile components loss, while viscosity parameters were determined with cone-plate digital rheometer. Potentiometric method was applied to measure pH of the produced hydrogels. The test for morphine sulphate pharmaceutical availability was performed with spectrophotometric method. Results: No basic differences were observed in the spreadability, the kinetics of water loss or in the measured pH values of model hydrogels produced with different cross-linking bases. Higher pharmaceutical availability of morphine sulphate was demonstrated from hydrogels with Carbopol Ultrez 10 having lower viscosity. The lowest pharmaceutical availability was obtained independently of the applied Carbopol for hydrogels in the prescription of which trietanoloamine was used. Conclusions: The most beneficial applicative properties (including rheological ones) were obtained for model hydrogels containing Carbopol Ultrez 10, but the kind of the cross-linking base practically did not affect the rate of morphine sulphate diffusion from the produced hydrogels.